Effects of Dietary Components on Testosterone Metabolism via UDP-Glucuronosyltransferase - Jenkinson, Carl; Petroczi, Andrea; Naughton, Declan P. (Frontiers in Endocrinology, 2013)
The potential interference in testosterone metabolism through ingested substances has ramifications for: i) a range of pathologies such as prostate cancer, ii) medication contra-indications, iii) disruption to the endocrine system, and iv) potential confounding effects on doping tests. Conjugation of anabolic steroids during phase II metabolism, mainly driven by UDP-glucuronosyltransferase (UGT) 2B7, 2B15 and 2B17, has been shown to be impaired in vitro by a range of compounds including xenobiotics and pharmaceuticals. Following early reports on the effects of a range of xenobiotics on UGT activity in vitro, the work was extended to reveal similar effects with common non-steroidal anti-inflammatory drugs. Notably, recent studies have evidenced inhibitory effects of the common foodstuffs green tea and red wine, along with their constituent flavonoids and catechins. This review amalgamates the existing evidence for the inhibitory effects of various pharmaceutical and dietary substances on the rate of UGT glucuronidation of testosterone; and evaluates the potential consequences for health linked to steroid levels, interaction with treatment drugs metabolised by the UGT enzyme and steroid abuse in sport.